The numerical analysis of hyperelastic properties in commercial and original aloe vera gels / Nur Nabila Mohd Nazali and Nor Fazli Adull Manan - Mohd Nazali, Nur Nabila; Adull Manan, Nor Fazli (Universiti Teknologi MARA, 2021)
A basic purpose of a good healing patch is to reduce the reproduction of bacteria in the wounded area with minimal effect of mechanical properties. This study focuses on the basic mechanical and biomechanical properties of the material for a healing patch application with a new composition of biodegradable ingredients by using the estimation of hyperelastic models to fit with the experimental data and the comparison between the commercial Aloe vera gels and original Aloe vera leaves. This project was started with a material selection which is gelatine and Aloe vera leaves as the main ingredient. Secondly, the specimen sets undergo a uniaxial tensile test to obtain the raw data. For numerical phases, the conventional theory of large deformation based on hyperelastic constitutive equations and Stress-Strain Energy Theory were identified. The final step for this project is curve fitting between experimental data (Ogden and Mooney-Rivlin hyperelastic models). New parameters were carried out for healing patch materials made of hybrid biomaterials from the hyperelastic theory. The Ogden and Mooney Rivlin trends were closely followed by the curve fit presented with a minor difference. Overall, the original Aloe vera leaves' values were Ogden (α=1.8792, µ=0.1881 Mpa) and Mooney-Rivlin (C1=0.0713, C2=0.0304) respectively. The significance of this project is to expand the knowledge about mechanical properties of natural polymers for wound healing application instead of depending on semi-synthetic polymers.